(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
This research study entitled “Role of Pratimarsh Nasya on Sukh Nidra-Prabodham (quality of sleep)” evaluates the effects of Pratimarsha Nasya on improving overall sleep quality in individuals identified as poor sleepers based on a Pittsburgh Sleep Quality Index (PSQI) score ranging from 5 to 10. The research study, explores the effectiveness of Pratimarsh Nasya, a traditional Ayurvedic therapy, in improving sleep quality among healthy individuals. A total of 150 participants were enrolled and divided into two groups: the intervention group (n=75) received two drops of Murchhit Til Tail (processed sesame oil) intranasally each evening as Pratimarsh Nasya, while the control group (n=75) followed standard sleep hygiene practices, including consistent bedtime routines and environmental adjustments. The intervention spanned a period of two months, during which both groups demonstrated significant improvement in sleep quality. Comparative analysis revealed that the Pratimarsh Nasya group experienced more immediate and pronounced improvement in sleep quality, as indicated by higher percentage relief. However, follow-up assessments suggested that the sleep hygiene group exhibited a lower recurrence of sleep disturbances over time. These findings suggest that Pratimarsh Nasya may offer an effective short-term strategy for enhancing sleep quality, while sleep hygiene practices contribute to more sustained, long-term benefits. No treatment related adverse events were reported in the study. Further research is recommended for underlying mechanisms and long term effects of Nasya therapy on sleep health.